PENGARUH SIKAP DAN NORMA SUBYEKTIF TERHADAP PERILAKU WAJIB PAJAK BADAN DI KANTOR PELAYANAN PAJAK PRATAMA GRESIK UTARA: TINJAUAN EMPIRIS ATAS IMPLEMENTASI THEORY OF REASONED ACTION - Kasbun, Kasbun (Fakultas Ekonomi Universitas Gresik, 2018)
This research analyzing variables impact in the Theory of Reasoned Action/TRA (Ajzen 1980) its attitude, subjective norm, that perceived by tax staff to tax obligation compliance agency. This research is exam too how the attitude and subjective norm giving direct impact to tax obligation compliance behavior agency with not using behavioral intention. This research sample is tax company staff as Tax Payer that registered on the Tax Service Pratama North Gresik Office. Research design is survey and instrument that is questionnaire use. Sample total is 100 tax staff. The test equipment used is Multiple Linear Regression. The results of hypothesis test showing is tax staff attitude giving negative impact and significant to tax obligation compliance behavior agency, that tax staff subjective norm giving positive impact and significant to tax obligation compliance behavior agency. This results same like with theory or research results from Hidayat (2010), Miladia (2010), Aini (2013), and Alvin (2014) that introduce of attitude and subjective norm influence with tax obligation compliance behavior.ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3477661